2005
DOI: 10.1037/0022-006x.73.4.763
|View full text |Cite
|
Sign up to set email alerts
|

The Course of Psychological Disorders in the 1st Year After Cancer Diagnosis.

Abstract: This study investigated the relationship between acute stress disorder (ASD) and posttraumatic stress disorder (PTSD) and comorbid anxiety, depressive, and substance use disorders over the first 12-month period following a cancer diagnosis. Individuals recently diagnosed with 1st onset head and neck or lung malignancy were assessed for ASD within the initial month following their diagnosis and reassessed for PTSD and other psychological disorders at both 6 months and 12 months following their cancer diagnosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
75
2
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 25 publications
2
75
2
4
Order By: Relevance
“…Other difficulties for patients with PTSD were also identified. Rates of prior mood (75%) and substance use disorders (33%) were high, a pattern similar to that found among head and neck and lung cancer patients with PTSD (Kangas et al, 2005;Kugaya et al, 2000). Both classes of disorders can be a sequelae of posttraumatic stress (Ozer et al, 2003).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Other difficulties for patients with PTSD were also identified. Rates of prior mood (75%) and substance use disorders (33%) were high, a pattern similar to that found among head and neck and lung cancer patients with PTSD (Kangas et al, 2005;Kugaya et al, 2000). Both classes of disorders can be a sequelae of posttraumatic stress (Ozer et al, 2003).…”
Section: Discussionmentioning
confidence: 53%
“…To date, four cancer studies have reported comorbidity rates for PTSD cases. Green and colleagues (1998) reported 11%, Mundy et al (2000) reported 28%, and Kangas et al (2005) reported up to 71% of their PTSD cases had concurrent depression. Mehnert and Koch (2007) reported that women diagnosed with cancer-related PTSD or acute stress disorder were more likely (Odds Ratio [OR] = 22.2) to have a comorbid disorder.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in an epidemiological survey exploring the prevalence of depressive symptoms among subjects of five biennial waves of the Health and Retirement Study, involving 8,387 individuals aged 51-61, subjects diagnosed with cancer had the highest hazard ratio of depressive symptoms within 2 years following initial diagnosis (HR 3.55; 95%, CI, 2.79-4.52), when compared to individuals diagnosed with diabetes, hypertension, heart disease, arthritis, chronic lung disease or stroke 20 . The chances of developing a new depressive episode following a diagnosis of cancer may be elevated in certain vulnerable groups (e.g., those patients with a previous history of depressive episodes), as suggested by an observational study exploring the relationship between acute stress disorder and subsequent depressive symptoms after a diagnosis of head/neck/lung cancer 21 . In this study up to 29% of individuals met the criteria for MDD within the first month after the diagnosis, of whom nearly one-third had a positive history for previous depressive episodes 21 .…”
Section: Epidemiological Links Between Depression and Cancermentioning
confidence: 99%
“…The chances of developing a new depressive episode following a diagnosis of cancer may be elevated in certain vulnerable groups (e.g., those patients with a previous history of depressive episodes), as suggested by an observational study exploring the relationship between acute stress disorder and subsequent depressive symptoms after a diagnosis of head/neck/lung cancer 21 . In this study up to 29% of individuals met the criteria for MDD within the first month after the diagnosis, of whom nearly one-third had a positive history for previous depressive episodes 21 .…”
Section: Epidemiological Links Between Depression and Cancermentioning
confidence: 99%